2014
DOI: 10.1371/journal.pone.0091063
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Intracellular HIV Nef to Endothelium Causes Endothelial Dysfunction

Abstract: With effective antiretroviral therapy (ART), cardiovascular diseases (CVD) are emerging as a major cause of morbidity and death in the aging HIV-infected population. To address whether HIV-Nef, a viral protein produced in infected cells even when virus production is halted by ART, can lead to endothelial activation and dysfunction, we tested Nef protein transfer to and activity in endothelial cells. We demonstrated that Nef is essential for major endothelial cell activating effects of HIV-infected Jurkat cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 57 publications
0
60
0
Order By: Relevance
“…Our and other groups [66, 68] have demonstrated Nef protein in endothelium of coronary and pulmonary arteries in SIV-HIV-Nef-infected macaques, which showed a relatively high percentage of blood cells constantly probing vascular endothelial cells [69], Thus, endothelial cells, especially those in developing atherosclerotic plaques, are constantly in direct contact with circulating monocytes and T cells and in prime physical position to receive Nef transfer. In the proinflammatory conditions associated with viremic and even aviremic HIV infection, endothelial cell activation leads to increased vascular adhesion protein and chemokine expression.…”
Section: Endothelial Dysfunction In Hiv Patientsmentioning
confidence: 91%
See 1 more Smart Citation
“…Our and other groups [66, 68] have demonstrated Nef protein in endothelium of coronary and pulmonary arteries in SIV-HIV-Nef-infected macaques, which showed a relatively high percentage of blood cells constantly probing vascular endothelial cells [69], Thus, endothelial cells, especially those in developing atherosclerotic plaques, are constantly in direct contact with circulating monocytes and T cells and in prime physical position to receive Nef transfer. In the proinflammatory conditions associated with viremic and even aviremic HIV infection, endothelial cell activation leads to increased vascular adhesion protein and chemokine expression.…”
Section: Endothelial Dysfunction In Hiv Patientsmentioning
confidence: 91%
“…In fact, transgenic mice expressing CD4-promoter-driven Nef develop a spectrum of pathologies including AIDS-like disease [64] and vasospasm in the heart [65], and certain Nef gene variants were linked to pulmonary hypertension [66, 67]. We have recently reported that HIV-infected T cells are more potent than free virus in activating coronary arterial endothelial cells [68]. There is evidence that this effect is Nef-dependent.…”
Section: Endothelial Dysfunction In Hiv Patientsmentioning
confidence: 99%
“…Tat Gp120 ↑ROS e [29] ↑oxidative stress h [28] ↑VCAM-1 e [29] ↑ICAM-1 a [30] ↓claudin-1 h [31] ↓claudin-5 h [31] ↓ZO-2 h [31] ↓occludin f [32] ↑apoptosis g [35] ↑oxidative stress h [28] ↓eNOS d [38] Nef Vpu Vpr ↑ROS d,e,i [41,42] ↑oxidative stress e,i [42] ↓eNOS e,i [42] ↑MCP-1 d [41] ↑apoptosis d [41] ↑VCAM-1 a [46] ↑apoptosis f [47] Proinflammatory cytokines TNF-a IL-6/CRP IL-1b ↑ROS a [61] ↓eNOS d [38] ↑ICAM-1 d,f [38,63] ↑ICAM-1 f [63] ↓eNOS a,b,c [80,81] ↓NO a,b,c [80,81] ↑ICAM-1 a,d [79] ↑VCAM-1 a,d [79] D ZO-1 a [82,83] D VE-cadherin a [83] ↑ICAM-1 a,f [63,70] ↑VCAM…”
Section: Hiv-proteinsmentioning
confidence: 99%
“…In vitro studies have shown the following proatherogenic effects of HIV viral proteins: A) Tat and gp120 induces expression of adhesion molecules [179, 180]; B) Nef and gp120 reduce endothelial NO production [181, 182]; C) Nef increases inflammatory cytokine release including IL-6 and TNF-alpha from macrophages [183]; D) Nef promotes MCP-1 secretion from endothelial cells [184]; E) Tat stimulates MCP-1 mediated monocyte transmigration [185]; F) Nef inhibits ABCA1-dependent CEC of macrophages [76]; G) Nef and gp120 may induce endothelial apoptosis, which could promote fibroatheroma rupture/erosion, resulting in formation of an acute thrombus [186, 187]; H) Tat stimulates IL-6 production from peripheral blood monocytes [188]. In vitro studies have also shown potential proatherogenic effects of specific ARTs including increased leukocyte adhesion to endothelial cells with efavirenz [189]; increased platelet reactivity with abacavir [190]; reduced cholesterol efflux from macrophages, decreased endothelial nitric oxide production, and endothelial cytotoxicity with ritonavir [191193]; and CD36-dependent cholesterol accumulation in macrophages with certain protease inhibitors [194].…”
Section: Figurementioning
confidence: 99%